EFFECT OF ADDING POLYVINYL ACETATE AND COCONUT SHELL ON CONCRETE - Vivaldi Octavianto R; Fredy Kurniawan; Diah Ayu W R (NAROTAMA UNIVERSITY, Indonesia)
Manufacture of concrete with a mixture of coconut shell and polyvinyl acetate. The material used in this study are from the coconut shell coconut waste treatment process which is crushed to a maximum size of 20 mm, whereas polyvinyl acetate condition is milky white emulsion. This study uses laboratory experiments concrete according to standards ISO 7656: 2012 for normal concrete and developed into concrete innovation. Coconut shell as a substitute for gravel with a rate of 8% and 10%, while the addition of polyvinyl acetate in the amount of 8% and 10%. At the time of fresh concrete workmanship, testing the slump test to control the workability and homogeneity. Treatment (Curing) specimen is done by covering the paper specimens with wet cement. Compressive strength testing carried out during the 28 days of the test specimen. The results obtained on the compressive strength with the highest average percentage of materials such as concrete polyvinyl acetate 8% and 8% of coconut shell Amounting to 351 kg/cm2 with an average density of 2199 kg/cm3. In each of the test object with a weight value is the quality efficiency in concrete polyvinyl acetate 8% and 8% of coconut shell.